Hubungan Risiko Patient Handling Dengan Keluhan Muskuloskeletal Pada Perawat Bagian IGD RSUD Dr. Moewardi Di Surakarta - Fatmawati, Arum Zurikah (2016)
Musculoskeletal is one of the occupational diseases which arise in hospital. This thing can be also happened to the nurse at dr. Moewardi Surakarta which partly have complaints on the part of skeletal muscle starts from very mild to weight. This condition can be also very bad by job performance as unnatural posture, workload, as well as individual factors. This study aims to know the relationship of risk by patient handling complaints musculoskeletal to nurse in part of IGD at dr. Moewardi Surakarta Hospital. This research method using observational design with cross sectional approach. The sampling technique uses purposive sampling with a sample of 20 respondents. Measurement of patient handling uses RULA and musculoskeletal measurement uses the NBM. The data analysis using Test Statistic Spearman Rank correlation (Rho) with a significant level (α = 0.05). The results for handling patient with musculoskeletal complaints obtained (p = 0.010) (r = 0.561), with a degree of closeness of the relationship is strong enough and shows a correlation to a positive direction, which means the higher the risk of patient handling, the greater of the risk of musculoskeletal disorders can be suffered by nurses.